CHARACTERISTICS OF TRADE AND ECONOMIC RELATIONS OF UZBEKISTAN WITH THE REPUBLIC OF BELARUS AT THE BEGINNING OF INDEPENDENCE (Scientific journal of the Fergana State University, 2023)
This article covers trade and economic relations between Uzbekistan and Belarus in 1991-2000. From the first years of independence, Uzbekistan has actively established trade and economic relations with countries and former allies in order to transition to a democratic market economy and economic development. The main reason for the active conduct of trade and economic relations with the Republic of Belarus from the former allies was the interdependence of industrial and manufacturing enterprises between the two countries. In 1991-2000, it was important to strengthen and intensify cooperation to develop the activities and increase the efficiency of large industrial and machine-building enterprises in Uzbekistan.